AKTIVITAS PENGHAMBATAN ENZIM ?-GLUKOSIDASE EKSTRAK BEBERAPA TUMBUHAN - Rahmanti, Adetya
Many plants have been used traditionally to treat diabetes mellitus. The major goal in the treatment of diabetes mellitus is to control blood glucose level close to normal, both fasting blood glucose and postprandial glucose levels. ?-Glukosidase is the enzyme that digests dietary carbohydrate, and inhibition of this enzyme could suppress postprandial hyperglycemia. The purpose of this study was to determine the inhibitory activity of ethanol extract of Andrographis paniculata NESS herb, Annona muricata L., Anredera cordifolia (Ten.) V. Steenis, Guazuma ulmifolia LAMK., Morinda citrifolia Linn., Orthosiphon spicatus B.B.S, Plantago major L, leaves dan Tinospora tuberculata Beumee stem on ?-glucosidase in vitro to evaluate its possibility as an antidiabetic agent. ?- glucosidase inhibitory activities of ethanol extract of eight plants was performed by Stop Rate Determination Spectrophotometric methode by measuring absorbance using a spectrophotometer at a wavelength of 400 nm. IC50 of three extracts that have the highest % inhibition was determined and Acarbose as comparator drug. Andrographis paniculata NESS herb, Annona muricata L., Anredera cordifolia (Ten.) V. Steenis Guazuma ulmifolia LAMK., Morinda citrifolia Linn., Orthosiphon spicatus B.B.S, Plantago major L leaves dan Tinospora tuberculata Beumee. stem extracts at concentration of 500 µg/mL have the ?-glucosidase inhibitory activity respectively 10.44 ± 0.44; 8.21 ± 0.11; 13.13 ± 0.43; 9.28 ± 0.44; 2.28 ± 0.71; 14.66 ± 0.56; 2.94 ± 0.22; dan 17.09 ± 0.58 (%). Acarbose as comparator drug at concentration of 500 µg/mL has ?-glucosidase inhibitory activity of 76.78 ± 0.54%. Tinospora tuberculata Beumee. stems, Orthosiphon spicatus B.B.S and Anredera cordifolia (Ten.) V. Steenis leaves extracts have the highest ?- glucosidase inhibitory activity with IC50 respectively 1892.21; 2470.05; dan 2528.89 (µg/mL).